A Model of Non-Uptake for National Immunization Program among Children Aged 0 - 3 Years in Southern Border Provinces: A Qualitative Study : Rohani Jeharsae - Nimu, Nisuraida; Jechrsae, Rohani; Somkird, Jinjuta; Sawan, Sarinee; Talek, Muhammad Fahmee; Wangkulam, Anat; Keethongmak, Kruawan (Princess of Naradhiwas University Journal, 2024)
This study aims to explore a conceptual framework and reasons of non-uptake for national immunization program among children aged 0-3 years in southern border provinces. A qualitative study was applied to achieve the research objective. Focus group discussion was derived from 3 groups of participants which were (1) parents (2) health care providers and (3) community leaders, religious leaders, health volunteers and women leaders with a total of 108 participants. The focus group discussion was done among 18 groups of participants from 6 districts in Pattani, Yala and Narathiwat. Tape recording and concept mapping was performed during the focus group discussion. Transcribing word-by-word was done by researchers, then thematic analysis was used to explore the research results. Trustworthiness was performed by presenting a summary of concept mapping to the participants immediately after finishing the focus group discussion. Themes and sub-themes were presented to participants, stakeholders, and experts with a total of 56. Results showed that the framework of non-uptake for national immunization program among children age 0-3 years included 1) vaccine hesitancy among parents related to fear of adverse reaction of vaccines, stress due to family disagreement and conflict, untrust on quality and efficiency of vaccines, belief in the will of Allah, vaccine is dirty agents and untrust on the vaccine ingredients (haram) 2) barriers of access caused by the difficulty in transportation and lacking of social support 3) insufficient service hours and incongruent service deliver with parent’s lifestyles, provider’s behaviors and ineffective follow up system. Besides focusing on parent’s hesitancy against vaccines, improving the accessibility of parents to vaccine services, service mild and follow up system is crucial attention to enhance vaccine coverage among children in the southern border provinces.